SUPER RABBIT RACERS! - Flintham, Thomas (New York, NY : Branches/Scholastic Inc., 2017)
Super Rabbit Boy is racing in the Super Grand Prix car race--but among the other racers is King Viking and his team of cheaters, and they will do anything to win.
Keywords: Superheroes -- Juvenile fiction; Animals -- Juvenile fiction; Children's stories